Synthesis and mesomorphism of fluoroalkylated platinum complexes - Bilgin-Eran, Belkiz; Ocak, Hale; Tschierske, Carsten; Baumeister, Ute (TAYLOR & FRANCIS LTD, 2012)
First examples of liquid crystalline chloro-bridged dinuclear platinum organyls carrying semiperfluorinated alkyl chains at their peripheries have been synthesised. The liquid crystalline properties were investigated using polarised optical microscopy, differential scanning calorimetry and X-ray scattering. Compounds with six semifluorinated chains and two alkyl chains show hexagonal columnar liquid crystalline phases with dramatically enhanced mesophase stabilities compared to the related hydrocarbon derivatives, which have only monotropic discotic nematic phases.
Keywords: liquid crystals; metallomesogens; fluoroalkylated metallomesogens; platinum organyls; ortho-metallation; ANTIFERROELECTRIC IMINE LIGANDS; LIQUID-CRYSTALLINE PROPERTIES; ORTHO-METALATED MESOGENS; MICRO-SEGREGATION; PALLADIUM(II) COMPLEXES; MOLECULAR-STRUCTURE; BLOCK MOLECULES; COLUMNAR; MESOPHASES; Chemistry; Crystallography; Materials Science